RENTAL PROGRAM APPLICATION SCREEN MOTOR SHIP IN PT. CITRA PUTRA MANDIRI JAYA USING MICROSOFT VISUAL BASIC 6.0 - Firmansyah Firmansyah; Hariyanto, SKom, MM Hariyanto, SKom, MM (Jurnal Sistem Informasi, 2002)
The use of computers in our lives have been popular in the community, not onlylimited in scope, but also in everyday life. In corporate environments, computers aretools that are absolutely necessary to achieve better results. At the company's motorsailing boat rental services required in the form of computer applications programsthat can assist in storage and transactions. All programs using Visual Basic 6.0programming language such as customer input program, edit programs customers, theprogram deletes pelangganm transaction program, the program reports, and programreceipt. By using a computer application program, the company will gain the ease infiling, preparing reports, making the supporting documents and other facilities toconduct their operations.